PENGARUH TONE AT THE TOP TERHADAP TEMUAN BERULANG DALAM LAPORAN HASIL PEMERIKSAAN BPK DENGAN EFEKTIVITAS TINDAK LANJUT REKOMENDASI SEBAGAI VARIABEL MEDIASI (Studi Kasus pada Pemerintah Daerah di Jawa Tengah yang Diperiksa oleh BPK) - Alifin Prima Ranidya; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of tone at the top on recurring findings in audit reports issued by the Audit Board of Indonesia (BPK). This study also investigates whether the effectiveness of audit recommendation follow-up acts as mediating variable in the relationship between tone at the top and recurring findings in BPK audit reports. The study employed a quantitative approach using secondary data obtained from local government financial audit reports of Central Java Province and the summary of semester audit results (IHPS) 1 and 2 for the 2021-2024 period. The sample selection was conducted using a purposive sampling method based on specific criteria, resulting in 99 observational data. The data were analyzed using multiple linear regression analysis, path analysis, and the Sobel Test. The results indicate that tone at the top has negative and significant effect on recurring findings, while the effectiveness of audit recommendation follow-up has a negative and significant effect on recuring findings. The mediation test results using the Sobel test show that the effectiveness of audit recommendation follow-up is able to mediate the relationship between tone at the top and recurring findings. This study demonstrates that tone at the top and the effectiveness of implementing audit recommendation follow-up play an important role in reducing recurring findings in local governments in Central Java.